2017
DOI: 10.1101/117564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drug Target Ontology to Classify and Integrate Drug Discovery Data

Abstract: Background: One of the most successful approaches to develop new small molecule therapeutics has been to start from a validated druggable protein target. However, only a small subset of potentially druggable targets has attracted significant research and development resources. TheIlluminating the Druggable Genome (IDG) project develops resources to catalyze the development of likely targetable, yet currently understudied prospective drug targets. A central component of the IDG program is a comprehensive knowle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

7
1

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 36 publications
(44 reference statements)
0
31
0
Order By: Relevance
“…Another relevant aspect of Kinome-wide classification models is how they perform across the kinase target protein target family, as defined here by the kinase groups. 20 Each kinase task was organized into its corresponding group (see methods) and model evaluation metrics were aggregated to discriminate differences in predictive performance. We observed that the multi-task models maintained high predictive performance across and within all kinase groups, even for those tasks that do not contain many active examples and are underrepresented globally (Supporting Figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another relevant aspect of Kinome-wide classification models is how they perform across the kinase target protein target family, as defined here by the kinase groups. 20 Each kinase task was organized into its corresponding group (see methods) and model evaluation metrics were aggregated to discriminate differences in predictive performance. We observed that the multi-task models maintained high predictive performance across and within all kinase groups, even for those tasks that do not contain many active examples and are underrepresented globally (Supporting Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…We compiled our kinase target prediction dataset by obtaining all publicly available kinase bioactivity data from ChEMBL (release 21), 23 a curated database of bioactivity measurements, and commercial kinase bioactivity data from KKB (release Q12016). 24 Using kinase domain annotations from the Drug Target Ontology (DTO) 20 we mapped domain information to UniProt, obtaining 485 unique UniProt identifiers. All UniProt IDs were mapped to ChEMBL release 21 target IDs and the corresponding KKB target ID.…”
Section: Dataset Aggregation and Constructionmentioning
confidence: 99%
“…All gene sets mentioned throughout this paper are available in the Supplementary Material. Future validation steps may include integration of chemical-protein annotation resources, using Pharos [48] and Chem-Prot [78], the use of a semantic model to evaluate druggability via the drug target ontology [79].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this is the fact that the current kinase inhibitors target not only a narrow range of targets, but also a narrow range of pathways including Angiogenesis, Cell Adhesion, Immune System Signaling (Cytokine, TCR, BCR) and anti-apoptotic pathways[10]. For example, all kinase inhibitors for renal cell carcinoma target angiogenic pathways [11]. It is probable that there exists a strategy for targeting multiple, orthogonal pathways that work in a synergistic manner, as opposed to targeting kinases with overlapping pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The CKI scores for each cancer for this kinase will be generated in table form, along with target development level, rank, kinase group and family and whether or not this kinase has an approved drug MOA. Many annotations from the Drug Target Ontology (DTO) [11] are available as facets to filter and select kinase targets. To start from a disease of interest, one can select a TCGA cancer in the “Disease” tab.…”
Section: Introductionmentioning
confidence: 99%